A Recognition Model of National Legal Pluralism in a Unitary State through the Prismatic Theory Approach - Jati Nugroho (HUMAYA Jurnal Hukum Humaniora Masyarakat dan Budaya, 2021)
The choice of a unitary state based on Article 1 Section 1 of the 1945 Constitution theoretically always relates to the factor of equality within the state. However, the choice of the Republic of Indonesia as a unitary state is based on the consideration of the pluralism aspects in terms of culture, language, customs, and ethnicity, which brings consequences for the recognition of applicable legal pluralism (Article 18B Section 2 of the 1945 Constitution). This study examines legal pluralism in a unitary state based on the prismatic theory approach to find out its legal recognition model. This study aims at finding an ideal legal pluralism recognition model in a unitary state which has tended to be centralized, such as the implementation of the Basic Agrarian Law that ignores the customary laws. The results of the legal prismatic theory approach are expected to able to fulfill justice in a pluralistic society. In this study, the researcher employed a normative juridical method through a political-law approach to various laws and regulations. Furthermore, the researcher also used a qualitative analysis. The results of this study showed as follows. (1) Politics of law as a guideline for legal development is inconsistent with Pancasila and legal systems that accommodate legal pluralism. As a result, customary law must comply with national law, which indicates the recognition of weak legal pluralism. (2) The recognition model of national legal pluralism through the prismatic theory approach by considering the plurality of the prevailing legal order may create certainty and benefit on the value of justice in society according to national ideology and Pancasila as the soul of the nation. The recommendations of this study are as follows. (1) Legal development should use the recognition model of national legal pluralism through the prismatic theory approach so that certainty and benefit on the value of justice in society can be established according to national ideology and Pancasila as the soul of the nation. (2) The prismatic theory approach can be an alternative solution to the recognition model of legal pluralism in realizing Indonesian national law based on Pancasila as the ideology and spirit of the nation.